2016
DOI: 10.1055/s-0042-120120
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-γ Agonists for the Treatment of Major Depression: A Review

Abstract: Selective agonists of the nuclear transcription factor peroxisome proliferator-activated receptor-gamma (PPAR-γ) are used for the treatment of type 2 diabetes. We reviewed their efficacy and safety for the treatment of major depression and the association of their potential antidepressant effects with changes in biomarkers of metabolism and inflammation. From 8 studies, 4 open-label trials, and 4 randomized controlled trials (RCT) (3 vs. placebo and 1 vs. metformin), 448 patients with major depression were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 58 publications
0
48
0
3
Order By: Relevance
“…Nonetheless, it is also possible that vortioxetine activates PPARγ directly in a 5‐HT‐independent fashion. This alternative hypothesis would be consistent with reports suggesting that PPARγ agonists may have antidepressant activity via their ability to reduce the levels of inflammatory cytokines such as IL‐6 and TNFα both in depressed patients and murine models of depression (Kemp et al ., 2014; Colle et al, ; ; Liao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is also possible that vortioxetine activates PPARγ directly in a 5‐HT‐independent fashion. This alternative hypothesis would be consistent with reports suggesting that PPARγ agonists may have antidepressant activity via their ability to reduce the levels of inflammatory cytokines such as IL‐6 and TNFα both in depressed patients and murine models of depression (Kemp et al ., 2014; Colle et al, ; ; Liao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, thiazolidinediones, including pioglitazone and rosiglitazone, are synthetic ligands that selectively bind at PPAR-γ and are used clinically for the treatment of diabetes [15]. However, given their side effects on weight gain, congestive heart failure, bone fractures, and macular and peripheral edema, the Food and Drug Administration (FDA) has limited their use [16]. PPAR-α synthetic ligands, including the fibrates (fenofibrate, clofibrate) (depicted in Figure 2) are characterized by a much safer pharmacological profile and are widely prescribed to lower high cholesterol blood levels and triglycerides [17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, metformin, a widely prescribed oral antidiabetic and slimming agent, has demonstrated little promise in this regard, and therefore, large‐scale studies are required before a decision concerning its repurposing could be made . In contrast, clinical trials showed that insulin sensitizer antidiabetic drugs activating peroxisome proliferator‐activated receptor gamma substantially reduced depressive symptoms in patients . For example, pioglitazone was found to enhance remission in patients with MDD or bipolar disorders .…”
Section: Drugs Repurposed or At The Prerepurposing Investigation Phasmentioning
confidence: 99%
“…[98] In contrast, clinical trials showed that insulin sensitizer antidiabetic drugs activating peroxisome proliferator-activated receptor gamma substantially reduced depressive symptoms in patients. [99] For example, pioglitazone was found to enhance remission in patients with MDD or bipolar disorders. [100] It was reported that pioglitazone mediated improvement in depressed patients probably through suppressing proinflammatory cytokines such as IL-6.…”
Section: Drug Repurposing: Principles and Techniquesmentioning
confidence: 99%